The effect of different soft drinks on the shear bond strength of orthodontic brackets. - M Omid Khoda; F Heravi; H Shafaee; H Mollahassani (Tehran University of Medical Sciences, 2012)
It is proved that acidic soft drinks that are commonly used, have an adverse effect on dental structures, and may deteriorate oral heath of our patients and orthodontic appliances. The aim of this study was to compare the effect of yoghurt drink with other soft drinks on the shear bond strength of orthodontic brackets.Seventy-five first premolar teeth extracted for orthodontic purposes were selected and standard twin metal brackets were bonded on the center of buccal surface with No-Mix composite. The teeth were thermocycled for 625 cycles and randomly divided into five groups of artificial saliva, carbonated yoghurt drink with lactic acid base, non-carbonated yoghurt drink with lactic acid base, 7 up with citric acid base and Pepsi with phosphoric acid base. In all groups, the teeth were immersed in liquid for five-minute sessions three times with equal intervening intervals for 3 months. SBS was measured by a universal testing machine with a speed of 0.5mm/min. Data was analyzed statistically by one-way ANOVA.The results showed that mean values for the shear bond strength of carbonated yoghurt drinks, non-carbonated yoghurt drinks, 7up and Pepsi groups were 12.98(±2.95), 13.26(±4.00), 16.11(±4.89), 14.73(±5.10), respectively. There was no statistically significant difference among the groups (P-value= 0.238)Soft drinks used in this study did not decrease the bond strength of the brackets bonded with this specific type of composite.